Neural pathways subserving face-based mentalizing - Yordanova, Yordanka Nikolova; Duffau, Hugues; Herbet, Guillaume (Brain Structure and Function, 2017)
Over the past few years, considerable progress has been done in clarifying the neural networks underlying mentalizing. However, although the cortical architecture of this function is relatively well understood, the white matter pathways that may be involved in conveying neural signals within the mentalizing network remain to be elucidated. To gain insight into this matter, a detailed stimulation mapping of face-based mentalizing was performed in 27 patients undergoing awake surgery for a right-sided diffuse low-grade glioma (DLGG). Direct electrical stimulation (DES) was applied to both the cortical and subcortical levels. In perfect agreement with previous literature using face-based mentalizing tasks, cortical sites were identified in the posterior inferior frontal gyrus (IFG), the dorsolateral prefrontal cortex (dlPFC), and the posterior superior temporal gyrus (pSTG). Most importantly, critical sites were found along the inferior fronto-occipital fasciculus (IFOF), and within the white matter fibres supplying the dlPFC. Disconnectome analyses confirmed the very high probability of IFOF disconnection during temporal subcortical stimulation, and revealed an additional implication of the superior longitudinal fasciculus/arcuate fasciculus (SLF/AF) during prefrontal subcortical stimulations. Altogether, these findings suggest that functional integrity of both the IFOF and the SLF is required for accurately inferring complex mental states from human faces.